2021
DOI: 10.1186/s13568-021-01213-9
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of royal jelly-mediated green synthesized silver nanoparticles

Abstract: The application of green synthesis in nanotechnology is growing day by day. It’s a safe and eco-friendly alternative to conventional methods. The current research aimed to study raw royal jelly’s potential in the green synthesis of silver nanoparticles and their antibacterial activity. Royal jelly served as a reducing and oxidizing agent in the green synthesis technology of colloidal silver nanoparticles. The UV–Vis maximum absorption at ~ 430 nm and fluorescence emission peaks at ~ 487 nm confirmed the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…To note that the IC50 value of sample A was not determined for S. aureus because the AgNPs were prepared using 300 µ M of AgNO3, tested starting from 46 µ M, and the Gram-positive strain are greatly resistant to AgNPs compared to E. coli. This finding has been previously reported for other Ag-based compounds [39,40] and it could be ascribed to a different interaction of the NPs with the bacterial cell wall of Gram positive and Gram-negative bacteria. S1).…”
Section: Antibacterial Assaysupporting
confidence: 84%
“…To note that the IC50 value of sample A was not determined for S. aureus because the AgNPs were prepared using 300 µ M of AgNO3, tested starting from 46 µ M, and the Gram-positive strain are greatly resistant to AgNPs compared to E. coli. This finding has been previously reported for other Ag-based compounds [39,40] and it could be ascribed to a different interaction of the NPs with the bacterial cell wall of Gram positive and Gram-negative bacteria. S1).…”
Section: Antibacterial Assaysupporting
confidence: 84%
“…The comparison between unfractionated, filtered, and isolated nanoparticles confirmed the antibacterial effectiveness of Growth data analysis showed that Gram-negative E. coli (Figure 6a, left) had a higher sensitivity than Gram-positive S. aureus (Figure 6a, right). Indeed, the cell wall structure plays a crucial role in the antibacterial activity of Ag-based compounds; it is well known that Gram-negative bacteria are more susceptible due to their narrower cellular walls compared to Gram-positive strains [62]. The purified Ag-PDA nanoparticles in fraction D completely inhibited E. coli when used at the highest dilution (1:10 with respect to the volume collected from the fractionation process) and with up to 24 h of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Here, 5 mL AgNP sol and 3 mL of E. coli or S. aureus suspension at a concentration of 10 7 CFU/mL were added to the sterile Luria-Bertani (LB) medium (LB, 5 g yeast extract, 10 g NaCl, 10 g tryptone, and 1000 mL water). The bacteria were cultured and maintained in LB broth and then incubated at 37 °C at 180 rpm, while the bacterial cell proliferation was monitored at intervals according to absorption at 600 nm [ 46 ]. Finally, the growth curve plot was created using the optical density (OD) value vs. time.…”
Section: Methodsmentioning
confidence: 99%